2016
DOI: 10.1158/0008-5472.can-15-2304
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Breast Cancer Models Mimic Hallmarks of Size-Induced Tumor Progression

Abstract: Tumor size is strongly correlated with breast cancer metastasis and patient survival. Increased tumor size contributes to hypoxic and metabolic gradients in the solid tumor and to an aggressive tumor phenotype. Thus, it is important to develop three-dimensional (3D) breast tumor models that recapitulate size-induced microenvironmental changes and consequently, natural tumor progression in real time without the use of artificial culture conditions or gene manipulations. Here, we developed size-controlled multic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
113
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(122 citation statements)
references
References 42 publications
8
113
0
Order By: Relevance
“…These non-adhesive microwell arrays enabled generation of uniform, defined size microtumors within 1–2 days using various HNC, breast and cervical cancer cell lines (Fig. 3B, C) [38, 39]. We have recently demonstrated the application of this platform technology to probe activation as well as inhibition of EGFR signaling in 3D HNC microtumors in response to EGF and cetuximab treatments, respectively [38].…”
Section: Polyethylene Glycol Dimethacrylate (Pegdma) Hydrogel Microwementioning
confidence: 99%
See 3 more Smart Citations
“…These non-adhesive microwell arrays enabled generation of uniform, defined size microtumors within 1–2 days using various HNC, breast and cervical cancer cell lines (Fig. 3B, C) [38, 39]. We have recently demonstrated the application of this platform technology to probe activation as well as inhibition of EGFR signaling in 3D HNC microtumors in response to EGF and cetuximab treatments, respectively [38].…”
Section: Polyethylene Glycol Dimethacrylate (Pegdma) Hydrogel Microwementioning
confidence: 99%
“…Another advantage of PEGDMA hydrogel microarrays is their ability to precisely control the microtumor size and thus, the physico-chemical factors in the tumor microenvironment [39]. When noninvasive breast cancer cells (MCF7, T47D) were cultured in non-adhesive PEG hydrogel microwells, precise control over microtumor size enabled controlled changes in tumor microenvironment in a reproducible manner recreating spatial distribution of proliferating and necrotic cells, the development of a hypoxic central core, up-regulation of hypoxia-inducible factor-1 alpha (Hif-1α) and pro-angiogenic vascular endothelial growth factor (vegf) and the overexpression of Glut-1 (metabolic stress marker) in large (600 μm) microtumors of breast cancer cell lines (Fig.…”
Section: Polyethylene Glycol Dimethacrylate (Pegdma) Hydrogel Microwementioning
confidence: 99%
See 2 more Smart Citations
“…The microwell-based spheroid culture method provides the following advantages over the hanging drop method and the other developed spheroid culture platforms: an extended culture period of 1030 days due to easy medium changes; ready for co-culture without direct cell-to-cell contact [30]; easy generation of size-controlled cell spheroids; easy growth medium changes in the device due to the shear-free and stress-free structure [31]; ready application to various cell types; and unlimited throughput, given that 361 cell spheroids can be obtained from a single device. Moreover, the microwell mimics the in vivo environment and contains CSC-secreted factors [32]. One recent study reported that round spheroids showed a signature of high mRNA expression for secreted molecules, which activate cell cycle-related signaling pathways and their downstream transcriptional regulators [33].…”
Section: Resultsmentioning
confidence: 99%